2009
DOI: 10.1177/1070496509347088
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change in the Caribbean: The Water Management Implications

Abstract: Concerns over the status of freshwater availability in the Caribbean region and in particular the eastern Caribbean states have been expressed for at least the past 30 years. There is a growing realization that availability will be vulnerable to extremes of climate behavior and increasing demand for water. Climate modeling for the Caribbean region under a range of scenarios suggests a continuation of a warming in average temperatures, a lengthening of seasonal dry periods, and increases in frequency of occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 15 publications
3
63
0
1
Order By: Relevance
“…A significant impact is observed in areas where the lens shrinks (i.e., along the periphery), as most settlements and the related infrastructure are typically near the coast on small islands (Ranjan et al, 2009;Cashman et al, 2010). As a result, any changes in the freshwater lens morphology within the coastal zone may affect access and availability of freshwater near the population centres.…”
Section: Long-acting Stressorsmentioning
confidence: 99%
“…A significant impact is observed in areas where the lens shrinks (i.e., along the periphery), as most settlements and the related infrastructure are typically near the coast on small islands (Ranjan et al, 2009;Cashman et al, 2010). As a result, any changes in the freshwater lens morphology within the coastal zone may affect access and availability of freshwater near the population centres.…”
Section: Long-acting Stressorsmentioning
confidence: 99%
“…Hence, interactive activities among them would exert positive influence on network effectiveness [40]. Non-state entities' participation in regional water governance could enhance the accessibility of the whole process [41], and citizen participation could supplement governments' effort on dealing with complex environmental issues [42].…”
Section: Water Governance Network Governance and Ecology Of Gamesmentioning
confidence: 99%
“…Damage to the nutmeg and cocoa industries due to hurricane Ivan in 2004 resulted in loss equivalent to 10% of Grenada's GDP (Mimura et al, 2007). Under future climate change, 46% of Caricom tourist resorts could be lost under a 1 m rise in sea-level (Moore, 2010;Simpson et al, 2010), while projected changes in temperature and rainfall will likely increase crop pests and diseases and the occurrence of extreme water stress (Nelson et al, 2009;Pulwarty et al, 2010;Simpson et al, 2010;Cashman et al, 2010). Past and future climate impacts on other key areas of Caribbean existence, for example, biodiversity and marine and coastal ecosystems (e.g., Fish et al, 2005;Donner et al, 2007;Hoegh-Guldberg et al, 2007;Chen et al, 2008) and on health and well being (e.g., Amarakoon et al, 2006;Chen et al, 2006;Ebi et al, 2006;Taylor et al, 2009) have also been studied and shown to be significant.…”
Section: Introductionmentioning
confidence: 99%